2015
DOI: 10.1002/14651858.cd009924.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Food supplementation for improving the physical and psychosocial health of socio-economically disadvantaged children aged three months to five years

Abstract: Food supplementation for improving the physical and psychosocial health of socio-economically disadvantaged children aged three months to five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 121 publications
2
100
0
2
Order By: Relevance
“…In 2012, the same authors (5) carried out a meta-analysis of community-based supplementary feeding in children under five years of age in lowincome and middle-income countries and concluded that supplementary feeding has a negligible impact on child growth. Even socioeconomically disadvantaged children, when supplemented, only grew an average of 0.27 cm more over 6 months than those who were not supplemented (6). The data did not question that severe starvation coincides with growth inhibition, but the net effect of nutrition on body height was generally small (7).…”
Section: Introductionmentioning
confidence: 85%
“…In 2012, the same authors (5) carried out a meta-analysis of community-based supplementary feeding in children under five years of age in lowincome and middle-income countries and concluded that supplementary feeding has a negligible impact on child growth. Even socioeconomically disadvantaged children, when supplemented, only grew an average of 0.27 cm more over 6 months than those who were not supplemented (6). The data did not question that severe starvation coincides with growth inhibition, but the net effect of nutrition on body height was generally small (7).…”
Section: Introductionmentioning
confidence: 85%
“…In 2012, the same authors [23] meta-analyzed community-based supplementary feeding in children under 5 years of age in low- and middle-income countries and concluded that though the scarcity of available studies still made it difficult to reach firm conclusions – there is a need for additional studies – supplementary feeding has a negligible impact on child growth. Kristjansson et al [24] showed in randomized controlled trials in socioeconomically disadvantaged children that even these children, when supplemented, only grew an average of 0.27 cm more over 6 months than those who were not supplemented. In a meta-analysis of 7 controlled before-and-after studies, they found no evidence of an effect on height, whereas meta-analyses of randomized controlled trials demonstrated benefits for weight-for-age z -scores.…”
Section: Catch-up Growthmentioning
confidence: 99%
“…In 2012, the same authors 11 meta-analysed community-based supplementary feeding in children under 5 years of age in low-and middle-income countries and concluded that although the scarcity of available studies still made it difficult to reach firm conclusions-there is a need for additional studies -supplementary feeding has a negligible impact on child growth. Kristjansson et al 12 showed in randomised controlled trials in socioeconomically disadvantaged children that even these children when supplemented only grew an average of 0.27 cm more over 6 months than those who were not supplemented. In a meta-analysis of seven controlled before-and-after studies, they found no evidence of an effect on height, whereas meta-analyses of randomised controlled trials demonstrated benefits for weightfor-age z-scores.…”
mentioning
confidence: 99%